STRATEGI PENGELOLAAN BARANG MILIK DAERAH DALAM MERAIH OPINI BADAN PEMERIKSA KEUANGAN WAJAR TANPA PENGECUALIAN PADA PEMERINTAH DAERAH PROVINSI BANTEN - Natta Sanjaya Natta Sanjaya (LPPM STIA Banten, 2016)
This research is entitled Strategy for Management of Regional Property in Achieving Reasonable Unqualified Opinion of the Supreme Audit Agency (BPK) in the Regional Government of Banten Province with a research focus on knowing and describing efforts or strategies for managing regional property in order to obtain the opinion of the Supreme Audit Agency (BPK). Unqualified (WTP) in the Regional Government of Banten Province. The results of the research show that the management of regional property in the Regional Government of Banten Province has not been fully implemented well. The management of regional property by the Regional Government of Banten Province, which has not been fully implemented well, is faced with several obstacles both in the areas of organization, apparatus resources, rules and management practices for managing goods which are not in accordance with existing regulations. The strategy for managing regional property belonging to the Banten Provincial Government in achieving an Unqualified Opinion (WTP) is carried out by continuing to validate and comprehensively inventory all SKPD assets; strengthen budget management systems and procedures related to asset procurement; socialize good governance of regional property and inancial governance in accordance with statutory regulations; carry out planned and sustainable asset management in accordance with clear BMD management stages; Information technology systems must have integrated e-audit facilities.